Evaluation of slag fertilizer potential in Capsicum annuum L. cultivation and production - Oumaima Ouala; Yasser Essadki; Hicham Khalisse; Hassan Chagiri; Abdelilah Meddich; Fatima El Khalloufi; Brahim Oudra (Journal of Agriculture and Environment for International Development)
The search for new approaches for sustainable and economic agricultural fertilization is becoming of great interest worldwide. The potential use of steel slag as a soil improver has been evaluated in this study to derive various benefits for agricultural cropping systems. Scanning electron microscopy (SEM), and inductively coupled plasma atomic emission spectroscopy (ICP-AES) confirmed their richness in minerals (Ca, Fe, Si, Mg, Mn, S, and P) beneficial for plant growth. In this regard, the objective of this study was to evaluate the effect of steel slag on the growth of Capsicum annuum L. plants. Three concentrations of slag (5, 20, and 30 g kg-1) were applied. Chlorophylls, carotenoids, mineral elements, and proteins content were then evaluated. The application of slag at 20 g kg-1 generated significant results on the growth parameters, namely, length of shoot (40.16 cm), root (22.16 cm), number of leaves (14 per plant), internodes (15 per plant), flowers and dry weights. Thus, this treatment allows the plants to reach fructification and form fruits of good nutritional quality as compared to the negative and positive (NPK fertilizer) control treatments. The application of the studied steel slag specifically at the concentration of 20 g kg-1 induced an increase in photosynthetic pigments (35.32 mg g-1 FW of total chlorophyll and 7.26 mg g-1 FW of carotenoids), essential elements (N, P, K and Ca) and a high level of proteins compared to the controls. The slag showed an improvement on C. annuum development and could be proposed as potential plant fertilizer to enhance crop productivity. Overall, the study confirms the importance of adopting appropriate sustainable practices when spreading slag on agricultural soils and monitoring its potential impact on the environment, particularly the risk of long-term metal release.